舰船用新型飞轮储能动发一体机综合物理场分析(英文) - 于雅莉 王元昔 张国胜 孙枫 (船舶与海洋工程学报：英文版, 2012)
A novel flywheel energy storage(FES) motor/generator(M/G) was proposed for marine systems.The purpose was to improve the power quality of a marine power system(MPS) and strengthen the energy recycle.Two structures including the magnetic or non-magnetic inner-rotor were contrasted in the magnetostatic field by using finite element analysis(FEA).By optimally designing the size parameters,the average speed of FEA results of was 17 200 r/m,and the current was controlled between 62 and 68 A in the transient field.The electrical machine electromagnetism design was further optimized by the FEA in the temperature field,to find the local overheating point under the normal operation condition and provide guidance for the cooling system.Finally,it can be concluded from the comprehensive physical field analysis that the novel redundant structure M/G can improve the efficiency of the M/G and maintain the stability of the MPS.